Adapting, correcting and sequencing movements: does working-memory capacity play a role? - Buszard, T.; Masters, R. S. W. (International Review of Sport and Exercise Psychology, 2018)
Interest in the role of working-memory capacity in everyday abilities has recently extended to the acquisition of motor skills. This review article examines the role of working-memory capacity in two areas of motor skill acquisition: (1) adapting and correcting movements in response to errors, and (2) sequencing movement patterns. Across a number of studies it was evident that individuals with low or underdeveloped working-memory capacity experienced diminished learning when the practice contexts placed high demands on working memory. Verbal working-memory capacity was associated with the ability to correct movement errors, while several studies revealed the importance of spatial abilities, including spatial working-memory capacity, when learning movement adaptations. Visuo-spatial working-memory capacity correlated with movement sequence learning, either explicitly or implicitly, but old age affected this relationship. Despite these correlations, however, our understanding of the relationship between working-memory capacity and motor skill acquisition is clouded by inconsistent results and a reliance on correlational analyses. To extend understanding of the role of working-memory capacity in motor skill acquisition, researchers should seek to explore novel experimental paradigms that bear closer resemblance to everyday tasks.